Reconstruction of the Mandibular Condyle - Anderson, Spencer R.; Pak, Kaitlynne Y.; Vincent, Aurora G.; Ong, Adrian; Ducic, Yadranko (Facial Plastic Surgery, 2021)
The mandibular condyle is an integral structure in the temporomandibular joint (TMJ) serving not only as the hinge point for mandibular opening, but also facilitating mandibular growth and contributing to facial aesthetics. Significant compromise of the TMJ can be debilitating functionally, psychologically, and aesthetically. Reconstruction of the mandibular condyle is rarely straightforward. Multiple considerations must be accounted for when preparing for condylar reconstruction such as ensuring eradication of all chronically diseased or infected bone, proving clear oncologic margins following tumor resection, or achieving stability of the surrounding architecture in the setting of a traumatic injury. Today, there is not one single gold-standard reconstructive method or material; ongoing investigation and innovation continue to improve and transform condylar reconstruction. Herein, we review methods of condylar reconstruction focusing on autologous and alloplastic materials, surgical techniques, and recent technological advances.
Keywords: mandible reconstruction; condyle reconstruction; free tissue transfer; alloplastic